Study on the effect of window opening on the drag characteristics of a car - Syed Mohamed Ali, Jaffar; Syed Muhammad, Kashif; Shaik Dawood, Mohd. Sultan Ibrahim; Omar, Ashraf Ali (Inderscience Enterprises Ltd., 2014)
In this study, the effect of window opening on the drag characteristics of a car is investigated. This additional aerodynamic drag can considerably affect the performance of a car in terms of instability, noise and fuel consumption. Using a 3D car model, the effect of window opening on the drag characteristics was numerically studied using STAR-CCM+ commercial CFD software. It was observed that the aerodynamic drag is highly influenced by the different window openings. For validation, a scaled down car model was tested in the IIUM Low Speed Wind Tunnel. The results obtained from both simulation and experimental data showed that the car with all windows open produced higher drag than a car with all windows closed. The experimental data from the wind tunnel test results was found to be in good agreement to the simulation counter part for the determination of drag coefficient for both window positions.